2011
DOI: 10.1055/s-0030-1256364
|View full text |Cite
|
Sign up to set email alerts
|

Nutzen und Sicherheit der Behandlung von Pleuraergüssen mit dem PleurX-Katheter: eine retrospektive Analyse

Abstract: ! Background:The purpose of this retrospective study was to investigate the efficacy and safety of an indwelling pleural device (PleurX, Denver Biomedical, USA) for the treatment of recurrent pleural effusions. In cases when life expectancy tends to be very short and also surgical decortication is not recommended, pleurodesis is another treatment option but requires complete drainage of the whole pleural fluid for optimal results which is sometimes hard to achieve. The PleurX catheter is an alternative therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In addition to having the advantage of decreased hospital stay,3,4 they have been shown to have similar, if not better, safety profile than pleurodesis,3,5,6 higher success rate with achieving pleural drainage and lesser time to symptom improvement 7. It is also preferred over pleurodesis in patients with MPE and poor performance status and poor prognosis, as well as in patients with trapped lung 3…”
Section: Discussionmentioning
confidence: 99%
“…In addition to having the advantage of decreased hospital stay,3,4 they have been shown to have similar, if not better, safety profile than pleurodesis,3,5,6 higher success rate with achieving pleural drainage and lesser time to symptom improvement 7. It is also preferred over pleurodesis in patients with MPE and poor performance status and poor prognosis, as well as in patients with trapped lung 3…”
Section: Discussionmentioning
confidence: 99%
“…Since its FDA approval in 1997, the IPC became the preferred method for managing recurrent MPEs on an outpatient basis [ Brubacher and Gobel, 2003 ]. Different studies have shown that it is at least as effective as chest tube and chemical pleurodesis in controlling MPEs [ Putnam et al 1999 , Blaukovitsch et al 2011 ], and that it is the preferred method to treat MPEs associated with trapped lung [ Efthymiou et al. 2009 ].…”
Section: Introductionmentioning
confidence: 99%